Clinical and microbiological profile of bacterial pathogens from patients with diabetic foot infections at a teaching hospital in the northeast China. (15th September 2022) - Ma, Lin-Lin; Li, Bin-Xian; Meng, Xue; Li, Ming-Cheng
Background: Diabetic foot ulcer infection (DFI) is a frequent complication of diabetes. Objective: The aim is to determine the clinical and microbiological profiles and the antibiotic resistance phenotype, analyze the DFIs risk factors. Methods: The present study is a retrospective, single-center study conducted at a teaching hospital in the northeast China. 242 cases of patients with diabetic foot disease Wagner grade 0–5 over 2 years were screened and the recovered data consisted of the clinical features, risk factors, etiology and drug resistant profiles. Results: The total percentage of Gram-negative rods (GNRs) and Gram-positive cocci (GPCs) was 138 (54.92%) and 113 (45.02%). The most common isolates were Pseudomonas aeruginosa and Staphylococcus aureus, accounting for 22.37% and 19.74%, respectively. Logistic regression analysis showed that the duration of ulcer, duration of antibiotic use, Wagner classification and osteomyelitis were risk factors for multi-drug resistant (MDR) bacteria infection ( p <0.05). Conclusion: The predominate pathogens of patients with DFI were GNRs, followed by GPCs in the region. They exhibited the different antibiotic resistance phenotype. The data provided advice on selection of highly sensitive antibiotics in the management of DFIs.